Effect of Transcranial Pulse Stimulation for the Treatment of Alzheimer´s Disease and its Related Symptoms - Fernández-Castaño, Ramiro; Fernández-Blázquez, Miguel Ángel; Echevarría Fernández, Iria; Cabrera-Freitag, Manuela; Freitag, Karin (Current Alzheimer Research, 2023)
Alzheimer's disease (AD) is the most common cause of neurodegenerative cognitive impairment. Brain stimulation techniques based on the delivery of transcranial shockwaves are currently being studied for their increasing popularity as an approach to modulate the human brain in a focal and targeted manner making this therapy a promising line of action against AD. In the present manuscript, we review for further understanding whether transcranial pulse stimulation (TPS) is a beneficial treatment for AD patients. PubMed, Google Scholar, and Cochrane databases were accessed with the search criteria set from year 2001 to 2022 and the following keywords were used: “transcranial pulse stimulation”, “focused ultrasound”, “noninvasive treatment and Alzheimer” and “TPS”. The search was focused on papers that provide evidence on the biological bases of the method, as well as its safety and tolerability. Even though more studies are needed with greater scientific rigor, such as a doubleblind and randomized study versus a placebo, TPS is an excellent and safe therapeutic option for AD. This novel approach accompanies currently available treatments and complements them, helping to maintain greater stability of the disease and slowing its progression. The biological effects and potential mechanisms of action of TPS for the improvement of cognitive function are further discussed.
Keywords: Alzheimer´s disease